Broadband Wireless Optical Nanolink Composed by Dipole-Loop Nanoantennas - Janilson Leao de Souza; Karlo Queiroz da Costa (IEEE Photonics Journal, 2018)
In this paper, a broadband wireless optical nanolink with plasmonic optical nanoantennas is theoretically proposed and analyzed. The nanolink is formed by linear dipole-loop nanoantennas for transmitter and receiver. The analysis is performed using the linear method of moments with equivalent surface impedance, where we apply a voltage source in the transmitting antenna and connect a load in the receiving antenna. The power received in the load is investigated as a function of frequency and distance between transmitter and receiver. In addition, a comparison is made between this wireless nanolink with a bifilar optical transmission line. The results show that the proposed nanolink, with dipole-loop nanoantenna, can increase the operating bandwidth in the range of 179.1–202.5 THz, when compared with conventional nanolink based only on dipole antennas. In addition, wireless nanolinks, based on dipole or dipole-loop antennas, are more suitable than wired nanolink for distances above approximately 22 μm.